2020
DOI: 10.3389/fmicb.2020.526545
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and Pharmaceuticals Structure Bacterial Core Communities in Urban and Montane Stream Biofilms

Abstract: Bacteria in stream biofilms contribute to stream biogeochemical processes and are potentially sensitive to the substantial levels of pollution entering urban streams. To examine the effects of contaminants on stream biofilm bacteria in situ , we exposed growing biofilms to experimental additions of nutrients [nitrogen (N), phosphorus (P), and iron (Fe)], pharmaceuticals (caffeine and diphenhydramine), nutrients plus pharmaceuticals, or no contaminants using contaminant exposure substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…In this work, a strong effect of diphenhydramine on biofilm-forming organisms was observed, where the decrease in rates of gross primary production and respiration was much greater than for other tested compounds, including ciprofloxacin. Ogata et al (2020) observed that a mixture of diphenhydramine and caffeine affected the taxonomic composition of stream biofilms (Table 1), although this was primarily through promoting unique taxa associated with contaminant tolerance and/or degradation, as caffeine and diphenhydramine, may have served as a carbon and/or energy source for taxa capable of degrading one or both compounds.…”
Section: In Situ Experimentsmentioning
confidence: 99%
“…In this work, a strong effect of diphenhydramine on biofilm-forming organisms was observed, where the decrease in rates of gross primary production and respiration was much greater than for other tested compounds, including ciprofloxacin. Ogata et al (2020) observed that a mixture of diphenhydramine and caffeine affected the taxonomic composition of stream biofilms (Table 1), although this was primarily through promoting unique taxa associated with contaminant tolerance and/or degradation, as caffeine and diphenhydramine, may have served as a carbon and/or energy source for taxa capable of degrading one or both compounds.…”
Section: In Situ Experimentsmentioning
confidence: 99%